Numerical investigation of flow characteristics and heat transfer performance in curve channel with periodical wave structure. (September 2019) - Zhang, L.Y.; Lu, Z.; Wei, L.C.; Yang, X.; Yu, X.L.; Meng, X.Z.; Jin, L.W.
Highlights: Curve channel with periodical wave structure is proposed to enhance heat transfer. Secondary flow in curve-wave channel generates more vortices disturbing main flow stream. Thermal boundary layer in curve-wave channel redevelops periodically along main flow direction. Heat transfer enhanced by curve-wave channel outweighs its pressure penalty. The optimum wave amplitude can be obtained by evaluating the dimensionless performance factor. Abstract: Flow and heat transfer in curve channel have been studied extensively due to the presence of the secondary flow induced by the centrifugal force. However, for the curved channel with small curvature, weakened centrifugal force reduces the intensity of secondary flow and heat transfer enhancement is attenuated accordingly. For sake of maintaining high heat transfer efficiency in curve channel with a wide range of curvature, periodical wave structure was introduced into the smooth-curve channel by this study. A three-dimensional model of the curve-wave structure was established and numerical simulation was carried out to explore the flow characteristics and heat transfer performance in the proposed channel. In addition, the effects of the wave amplitude on the channel performance were analyzed. The results showed that the heat transfer of smooth-curve channel can be enhanced remarkably by applying wave structure on the channel wall, and the overall performance factor indicates that the heat transfer argumentation outweighs the pressure loss penalty. It was also found that the heat transfer in the curve-wave channel can be further enhanced by increasing wave amplitude. The most effective heat transfer enhancement can be achieved based on the evaluation of the overall performance factor.